FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PETUGAS LAPANGAN PADA DINAS LINGKUNGAN HIDUP DAN KEBERSIHAN KEC. ALAK, KOTA KUPANG - Msyukur Dwi Riansyah; Puji Muniarty; Chiristin Mariana Kameo (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2026)
This study aims to examine the association between work motivation, work discipline, and work facilities and the performance of field officers at the Kupang City Environmental and Sanitation Office (DLHK). A quantitative research method with a causal associative approach was employed. Data were collected through questionnaires distributed to 80 field officers selected using proportional random sampling from a total population of 400 officers. The data analysis technique used was multiple linear regression analysis to test the partial and simultaneous associations between work motivation, work discipline, and work facilities with officer performance. Prior to regression analysis, data were tested through validity tests, reliability tests, and classical assumption tests. The results showed that work motivation, work discipline, and work facilities each had a positive and statistically significant association with the performance of field officers at DLHK Kupang City. The partial test results showed that work motivation had a calculated t-value of 4.976 (sig. = 0.000), work discipline had a t-value of 3.976 (sig. = 0.000), and work facilities had a t-value of 4.142 (sig. = 0.000). The simultaneous test showed that the three variables jointly had a significant association with officer performance, with an F-value of 239.695 (sig. = 0.000) and an Adjusted R Square value of 0.901 (90.1%). These findings indicate that the three variables together explain 90.1% of the statistical variation in officer performance, while the remaining 9.9% is associated with other variables outside the model. Given the cross-sectional survey design, findings reflect statistical associations rather than experimental causation.